A study into the propensity for exhaust gas ingress into a vehicle as a result of collision damage. (2015) - Henderson, Brian; Hall, Mike; Hoyes, Philip
In a low-speed collision when a vehicle is struck in the rear, certain types of damage may occur that cause a breach between the interior of the vehicle and the outside atmosphere. In the presence of these types of damage it is often thought that the vehicle's own exhaust gases may be able to enter the interior of the vehicle. As a consequence that vehicle may be deemed unsafe for continued use. This report describes an investigation into the ingress of carbon monoxide and, by implication, other exhaust gas components into the interior of a vehicle through areas of simulated damage at the rear. The results indicate the propensity of exhaust gas ingress to the interior of a vehicle.